United we stand: a history of Britain's trade unions - Reid, Alastair J. (New York, 2005)
"Previous histories of the British trade unions have tended to treat the working class as a single entity. This gave workers' identity a coherence and dignity, but it also made them separate from and excluded from the rest of British society. In this highly original and absorbing new book Alastair Reid discards this entire model, preferring to see working people' as integral to British society as a whole. Looking both at individual workers and their fates and at the often vast organisations that have represented them, Alastair Reid, in this fundamentally important book, shows how unions have throughout the modern era always been a crucial element in British life and that all governments have - whether they like it or not - had to develop policies to deal with them."